Cardiovascular Risk Profile in Dupuytren’s Disease: A Systematic Review and Meta-Analysis - Mathieu, Sylvain; Pereira, Bruno; Dutheil, Frédéric; Tournadre, Anne; Soubrier, Martin (Cardiology and Cardiovascular Medicine, 2024)
Objective: Patients with Dupuytren’s disease (DD) have a higher cardiovascular (CV) risk. It is difficult to know if this excess is linked to genetic factors or to a higher frequency of CV risk factors such as diabetes. We aim to assess the cardiovascular profile of DD patients by a metaanalysis on their CV risk factors and the country where the study was done. Methods: We performed a SLR up to June 2023. Differences between DD patients and controls were expressed by standardized mean differences using inverse of variance method or odds ratio by Mantel-Haenzel method. Results: We obtained 79 references, which corresponded to 114,446 DD patients and 2,597,950 controls. We found a higher risk of CV death (OR=1.33 [95%CI:1.07-1.66]) in DD compared with controls. DD Patients were more often diabetics (OR=4.06 [95% CI:3.07-5.37]). In 43 studies, incidence of DD was found in 15.5% of diabetic patients (11.9-19.5%). DD patients were older, more often men, smokers or alcohol drinkers. Levels of blood pressure, total cholesterol or triglycerides were not different in DD and controls. The risk of obesity was significantly lower in DD. The country where the study was done had no impact on these results. Conclusion: We found a higher CV risk in DD that seemed not to be linked to genetic factors but rather to CV risk factors. Assessment of cardiovascular risk is important in DD patients, with especially search of diabetes or alcohol consumption but also other cardiovascular risk factors that might thereafter be well-controlled.